Macro-correlates of inmate violence: the importance of programming in prison order - Randol, Blake M. (The prison journal, 2017)
Identifying the facility-level correlates of inmate misconduct is necessary for improving safety for both inmates and staff. Assessing these factors is also critical to ensure the effectiveness of administrative controls and facility programming. Using a repeat measures analysis, this study examines a panel of 487 state correctional facilities to assess the dynamic effects that factors of administrative control and treatment availability have on inmate-inmate and inmate-staff assaults. Findings show that several types of facility programs were negatively associated with inmate-inmate assaults but not inmate-staff assaults. Also, several dimensions of administrative control were associated with inmate-staff assaults. Implications for research and correctional practice are discussed.